Nilai taksonomi trikom dalam Genus Neesia (Bombacaeae) - Noraini Talip; Salmizawati mohamad Salim, Richard Chung Cheng Kong (Universiti Kebangsaan Malaysia, 2009)
A study was undertaken on the presence and trichomes types in five Neesia species of Bombacaceae. Results showed that the presence of dendritic, glandular, simple unicellar, peltate scale and stelate trichomes in Neesia. The presence of stelate trichome can be used as a diagnostic character in Neesia malayana, peltate scale trichomes in Neesia altissima and simple unicellular trichomes in Neesia piliuliflora. The presence of glandular trichomes is a common character in all species studied. Dendritic trichomes has little taxonomic value but yet can be used in distinguishing species. As a conclusion the presence of trichomes in leaf lamina in Neesia has taxonomic value especially at the species level.